PERAN MAHASISWA MAGANG KUA DALAM PENGUATAN AKTIVITAS MAJELIS TA‘LIM MASYARAKAT DI KECAMATAN MEDAN PERJUANGAN - Aisyatur Rahmah Wiwana; Ahmad Taufik Alfarizi Siagian; Lembayung Aurandyta; Nurul Khaidah; Putri Sagita Anugrah Aini; Wahidatul Husna; Yarsha Ardhana Harahap (STKIP Subang, 2026)
Majelis Ta'lim (Islamic boarding schools) are non-formal religious educational institutions that play a strategic role in fostering Islamic values in the community. The Office of Religious Affairs (KUA), as a government institution in the religious field, plays an active role in supporting and developing Majelis Ta'lim activities at the sub-district level. This study aims to analyze the role of KUA student interns in strengthening the activities of Majelis Ta'lim in the Medan Perjuangan sub-district. This study uses a qualitative approach with descriptive methods, through observation, interviews, and documentation. The results show that KUA student interns play a role in educational, administrative, social, and innovative aspects, such as mentoring religious activities, preparing study materials, managing Majelis Ta'lim administration, and introducing more communicative and contextual learning methods. These roles contribute positively to improving the quality, sustainability, and community participation in Majelis Ta'lim activities. Thus, the presence of KUA student interns is a significant supporting factor in optimizing the function of Majelis Ta'lim as a means of community religious development.